Peritonsillar and deep neck infections - Prospective study - Estêvão, Roberto (2014)
Objectives: To evaluate and establish a relation of the demographic, symptomatic, analytical, microbiological and outcome characteristics of hospitalized patients with peritonsillar and deep neck infection. Material and methods: A prospective study of patients admitted to the Hospital of Guimarães from March 2011 to March 2012 with the diagnosis of peritonsillar or deep neck infection. Results: During the study period 47 patients were hospitalized, 24 males and 23 females. The average age of the patients was 31.7 ± 17.3 years. A total of 24 microbiological cultures were carried out. Most abscesses had group A beta-hemolytic streptococci etiology. Conclusions: The data are consistent with the literature. The study highlights the importance of the elimination of risk factors for these infections. The value of C reactive protein and the type of infection is correlated with the duration of hospitalization.